FACTORS INFLUENCING INVESTORS TO ADOPT THE SHARIA ONLINE TRADING SYSTEM : AN EMPIRICAL EVIDENCE IN THE ISLAMIC INDONESIAN STOCK EXCHANGE - Thasrif Murhadi; Muhammad Yamin; Amelia Rahmi; Naifa Fajarna (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The study aims to identify the factors influencing the intention to adopt Sharia Online Trading System (SOTS) by stock investors in Indonesia. It uses structured questionnaires for data collection. Moreover, the data is obtained from the sharia stock investors using SOTS for stock trading. Out of 385 questionnaires completed by the respondents, only 336 were usable. The data was then processed using SEM Amos. The results of the study show that perceived usefulness, social norm and relative advantage have a positive and significant effect on the adoption of SOTS by stock investors. However, perceived ease of use and perceived riskiness do not have a significant effect on the adoption of SOTS by stock investors. For more diverse results, future researchers can expand the scope of respondents. Another factor, i.e., religiosity, can be used as a moderation in future research; it also needs to be explored by adding other variables such as trust, perceived cost, etc. This study provides some information about the factors influencing the intention to adopt SOTS by stock investors. In addition, the results of this study can be a reference for stock brokers in developing SOTS to attract more stock investors to adopt SOTS. Furthermore, for stock market regulators, they can make policies and regulations to encourage the increased use of SOTS. According to the literatures read by the author, there is no previous research discussing the factors that influence the adoption of SOTS in the sharia stock market.